Presmoothing the Aalen-Johansen estimator in the illness-death model - Moreira, Ana (2013)
One major goal in clinical applications of multi-state models is the estimation of transition probabilities. The usual nonparametric estimator of the transition matrix for non-homogeneous Markov processes is the Aalen-Johansen estimator (Aalen and Johansen 1978 [1]). In this paper we propose a modification of the Aalen-Johansen estimator in the illness-death model based on presmoothing. The consistency of the proposed estimators is formally established. Simulations show that the presmoothed estimators may be much more efficient than the Aalen-Johansen estimator. A real data illustration is included.